PEMETAAN POTENSI PERTAMBANGAN BAHAN GALIAN PASIR DAN BATU DI WILAYAH KECAMATAN JAILOLO TIMUR KABUPATEN HALMAHERA BARAT - Karim, Razak (Fakultas Teknik UMMU, 2019)
ABSTRACT The availability of data and information on the potential of mineral resources has a very important role in supporting investment in mining business activities. To realize this, the researchers collaborated with the West Halmahera District Government to conduct an investigation of Potential and Mapping Identification of the Sand and Stone Minerals Areas, especially in East Jailolo Subdistrict. The problem is how to provide basic data information regarding the potential of the existing minerals on site, both for the government, the private sector, businessman and the public community. And how potential of the minerals can be utilized optimally in the context of increasing mining business activities, and increasing Regional Original Income. The methodology and scope of this activity is to identify potential locations for economical of minerlas extraction. Technically, a study of the potential preparation of minerals is carried out through research and analysis of rock samples and conditions at the location of the investigation include geological, technical and distribution aspects. From the results of field investigations and analysis of actual conditions obtained; (1) At the location of the investigation found several types of potential rock and sand minerals in the form of volcanic rocks, the availability of which is almost completely spread throughout the investigation area. (2) These volcanic rocks are acidic to intermediate rocks, some of which are found fresh, and some are weathered. (3) This rock is found in the steep morphology of the hills to be very steep because of the very good condition of the rock characteristics. (4) The characteristics of these rocks include ; has water resistance, spesific gravity of 2.3-2.7 and compressive strength of 600–2400 kg/cm2, where these volcanic rocks can be used as home foundations materials, stone temples/ornamental stones, road coatings and foundations, and for other building materials. From the results of the investigation it is recommended that all parties manage the potential of the stone and sand, this can be done to provide income in the form of taxes and levies to the regional government.